Comparative Study of Zakat and Dana in the Qur'an and Tripitaka: An Offer of Interfaith Dialogue - Zahrah, Ummuz (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
Diversity in religion is inevitable. Zakat and Dana are concepts of giving in Islam and Buddhism that show diversity in religious approaches to the value of giving. This paper starts with three important questions: a) How are the concepts of zakat and dana in the Qur'an and Tripitaka? b) What are the similarities and differences between zakat and dana in the Qur'an and Tripitaka? c) How does the comparison of Zakat and Dana in the two books realize interfaith dialogue? The findings in this article show that both the Qur'an and Tripitaka provide guidance related to the concept of giving as a universal value. Both teach the importance of sharing as a form of goodness that supports the welfare of individuals and society. The differences between zakat and dana lie in their nature, implementation, and religious dimensions that can complement each other. This study shows that zakat and dana can be platforms for dialogue between religious communities. The diversity in these two religious traditions can strengthen tolerance and harmony.